Public Employment Services and Strategic Action towards Rural NEETs in Mediterranean Europe - Daniela Marzana; Adriano Mauro Ellena; Sara Martinez-Damia; Ana Sofia Ribeiro; Isabel Roque; João Carlos Sousa; Omeed Agahi; Maria Isabel Pell Dempere; Òscar Prieto-Flores (Social Sciences, 2023)
The NEET phenomenon in southern Europe is particularly alarming. Most studies have focused on analysing the socio-demographic characteristics of NEET and policies directed towards them, but more research is needed regarding the psychological aspects that underlie this condition. This paper, grounded in the bioecological model, aims to analyse the psychological dimensions regarding the functioning of Public Employment Services (PESs) in three countries that rely on the South Mediterranean welfare model. Between November 2022 and September 2023, research was conducted across six rural PES locations in Italy, Spain, and Portugal, based on interviews and focus groups with PES operators and young NEET users. Thematic analysis identified two central axes: Enhancing Relationships and Building Strategic Action, which were crucial for improving NEET-PES interactions and fostering connections between PES and other community entities. The results highlighted the importance of psychological elements in the effective involvement of NEETs in policy initiatives.